Health Literacy and Behaviors of Patients and Caregivers Related to Glycemic Control Among Individuals With Type 2 Diabetes in Chiang Mai Province, Thailand - Chaimongkon S; Sakulwattana W; Ong-Artborirak P; Liyanage E; Seangpraw K (Patient Preference and Adherence)
Siranee Chaimongkon,1 Wannita Sakulwattana,1 Parichat Ong-Artborirak,2 Esther Liyanage,3 Katekaew Seangpraw1 1School of Public Health, University of Phayao, Phayao, 56000, Thailand; 2Department of Research and Medical Innovation, Faculty of Medicine Vajira Hospital, Navamindradhiraj University, Bangkok, 10300, Thailand; 3Department of Physiotherapy, Faculty of Allied Health Sciences, University of Peradeniya, Augusta Hill, Sri Amarawansa Mawatha, Kandy, 20400, Sri LankaCorrespondence: Katekaew Seangpraw, School of Public Health, University of Phayao, Phayao, 56000, Thailand, Email eungkaew@gmail.comBackground: The impact of caregivers’ health literacy (HL) and patient care behaviors on glycemic control in type 2 diabetes mellitus (T2DM) is not well known.Purpose: This study examined the HL and behaviors of both patients and caregivers in relation to glycemic control among T2DM patients.Methods: A cross-sectional study in Fang district, Chiang Mai Province, involved 305 T2DM patients aged over 45 and their caregivers, selected through simple random sampling. Data were collected via questionnaires, and blood samples were analyzed for fasting blood sugar (FBS) and glycated hemoglobin (HbA1c).Results: The findings revealed that most patients and caregivers had diabetes HL scores at the functional literacy level (53.77% and 37.05%, respectively). The majority of patients scored moderately in self-care behaviors (SCB) at 76.10%, while caregivers’ patient care behaviors also scored moderately at 68.20%. Mean FBS and HbA1c levels were 129.81 mg/dl and 7.3%, respectively. Linear regression analysis showed that, after adjusting for sex, age, education level, financial status, duration of diabetes, smoking, and alcohol consumption, FBS was significantly associated with patients’ HL (Beta = − 0.161), SCB (Beta = − 0.197), caregivers’ HL (Beta = − 0.217), and caregivers’ patient care behaviors (Beta = − 0.181). Similarly, HbA1c was significantly correlated with patients’ HL (Beta = − 0.265), SCB (Beta = − 0.233), caregivers’ HL (Beta = − 0.255), and caregivers’ patient care behaviors (Beta = − 0.200).Conclusion: These results highlight the importance of enhancing health literacy (HL) and behaviors in both patients and caregivers to achieve optimal glycemic control, underscoring the need for caregivers to develop strong HL skills and improve their competencies in effectively managing T2DM.Keywords: health literacy, self-care behavior, diabetes mellitus, glycemic control, caregiver